The Future of Architecture: Another Episode in Cultural History or the Return of the Object? - David Howard Bell (Oz, 1981)
At some ephemeral shining moment on its path to ruin a collapsing building reveals a maximum of truths about itself. Many of these are simply invisible when the building exists as a static whole…